Deposition of Lu-Fe-O thin films on silica glass substrates by MOCVD - Cardoso, A. F. (2020)
Thin films of the Lu-Fe-O system were deposited by aerosol assisted MOCVD on silica glass substrates. Hexagonal h-LuFeO3, garnet Lu3Fe5O12, perovskite o-LuFeO3 or hematite Fe2O3 phases were obtained, depending on the thermodynamic deposition conditions or post annealing temperature. Magnetic measurements confirm the ferromagnetic behaviour at room temperature of the thin films with garnet phase. An indirect bandgap of 1.78 eV was measured.